2004
DOI: 10.1051/0004-6361:20040477
|View full text |Cite
|
Sign up to set email alerts
|

Detection of neutral sodium above Mercury during the transit on 2003 May 7

Abstract: Abstract. The extent of the exosphere of Mercury above the planet's limb could for the first time be observed by detecting an excess absorption in the solar sodium line D 2 during the transit of Mercury across the solar disk on 2003 May 7. The observations were performed with a 2d Fabry-Perot spectrograph of the Vacuum Tower Telescope at Izaña, Tenerife. The absorption excess, blue-shifted by 13 pm relative to the solar line, is mainly concentrated near the polar regions. There, the absorption excess can be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 18 publications
(19 reference statements)
5
83
4
Order By: Relevance
“…Dawn/dusk asymmetry is also significant in the case of PSD as seen in Figure 4 panels b and f. This is the case because PSD dominates when the velocity of the terminator is maximum around Mercury's aphelion. In Figure 3, a clear dawn/dusk asymmetry is apparent between TAA=110° and 240° roughly where the PSD enhanced simulation predicts such an asymmetry and where Schleicher et al (2004) observed it (at TAA=150°).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Dawn/dusk asymmetry is also significant in the case of PSD as seen in Figure 4 panels b and f. This is the case because PSD dominates when the velocity of the terminator is maximum around Mercury's aphelion. In Figure 3, a clear dawn/dusk asymmetry is apparent between TAA=110° and 240° roughly where the PSD enhanced simulation predicts such an asymmetry and where Schleicher et al (2004) observed it (at TAA=150°).…”
mentioning
confidence: 77%
“…
AbstractOur understanding of Mercury's sodium exosphere has improved considerably in the last 5 years thanks to new observations (Schleicher et al 2004) and to the publication of a summary of the large set of ground based observations (Potter et al 2008;2007;. In particular, the non-uniformity in longitude of the dayside sodium distribution (the dawn/dusk asymmetry) has now been clearly observed.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ground-based observations by Bida et al (2000) reveal Ca I emission in the resonance line at 4226.74 Å. Observations performed during the transit of Mercury in 2003 detected additionally sodium emission lines (Na I D 1,2 ), which allowed Schleicher et al (2004) to trace the extent of the exosphere of Mercury above the planet's limb. Potter et al (2002) observed a sodium-tail in the anti-sunward direction extending ten's of planetary radii.…”
Section: The Mercury Analogymentioning
confidence: 99%
“…For example, during the Mercury transit in 2003, neutral sodium in its exosphere was detected using this technique (Schleicher et al 2004). Even the Earth can be investigated as a transiting planet during lunar eclipse observations, when we can study the absorption lines of major atmospheric constituents such as CH 4 , H 2 O, O 2 , O 3 , and CO 2 in reflected light from the Sun by the Moon (see e.g., Pallé et al 2009;Vidal-Madjar et al 2010).…”
Section: Introductionmentioning
confidence: 99%